1, 6-Conjugate sulfonylation of para-quinone methides: An expedient approach to unsymmetrical gem-diarylmethyl sulfones. Issue 3 (17th January 2019) - Guan, Xiao-Yu; Zhang, Liang-Dong; You, Peng-Sheng; Liu, Sheng-Shu; Liu, Zhang-Qin
Graphical abstract: Highlights: A novel sulfonylation of para -quinone methides with sodium arylsulfinates. An inexpensive and efficient synthesis of unsymmetrical gem -diarylmethyl sulfones. High functional group tolerance, and scalability (gram scale). Further transformation of the diarylmethyl sulfones were also demonstrated. Abstract: A novel sulfonylation of para -quinone methides with sodium arylsulfinates has been developed via acetic acid promoted sulfa-Michael addition. This reaction provides an inexpensive and efficient method to synthesize various unsymmetrical diarylmethyl sulfones, displaying the advantages of high atom economy, good functional group tolerance, scalability, and environmentally friendly operation. Derivations of target products are also demonstrated.